Rachel Chance - Thesman, Jean. (Boston : Houghton Mifflin, 1990)
When Rachel's illegitimate baby brother is kidnapped by a travelling band of revivalists in 1940, she sets out with her grandfather, a hired hand, and an eccentric neighbor in a desperate attempt to steal him back.
Booklist.
Horn Book.
School Library Journal.
6.9.
6.9
5-8
Keywords: Kidnapping -- Fiction; Kidnapping -- Fiction; Washington (State) -- Fiction; Washington (State) -- Fiction